Perceptions, awareness and acceptance of library 2.0 applications among librarians at the International Islamic University Malaysia - Mansor, Yushiana; Idris, Suby Rabea Adawiyah (University of Tehran, 2010)
The paper has investigated the perceptions, level of awareness, and acceptance of Library 2.0 applications among librarians at the International Islamic University Malaysia (IIUM). The paper also identified perceived factors and problems that could influence successful implementation of Library 2.0. The findings showed that there was high awareness among the librarians with Library 2.0 applications. The findings also indicated that there was high level of computer expertise among the respondents in terms of web browsers and search engines, in addition to high level of utilization in some of the Web 2.0 applications. In addition, the study observed high rates of using blogs and Wikipedia among the librarians. Though the librarians hold positive perceptions on library 2.0 applications, and indicated willingness to learn more on the utilization of 2.0 tools, they highlighted several concerns in implementing Library 2.0.